1973
DOI: 10.2105/ajph.63.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Drug overdoses in a Canadian city.

Abstract: Data on drug overdoses are collected from emergency rooms of all general hospitals in Hamilton, Ontario over a 15-month period. High proportion of patients had been diagnosed as depressed, many are alcohol dependent or intoxicated. A large majority were female. Findings are discussed and practical applications are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar findings are described in the medical literature. 2,8,14,16,29,33,49,56,59,64,69,71,73,75,76,82,87,90,91,94,104,108,110,113 Despite substantial differences in characteristics of the patient populations and in criteria for inclusion, numerous clinical studies of the incidence and Year(s) 1957-19671968-19701967-1971-1970Not stated 1966-19671960-1965-19711968-196419681970-197119701971-1967-1964 consequences of acute overdosage from around the world indicate that benzodiazepine ingestion accounts for a substantial proportion of cases of drug overdosage in adults (Table V). Findings from series describing time-related changes in patterns of drug ingestion…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings are described in the medical literature. 2,8,14,16,29,33,49,56,59,64,69,71,73,75,76,82,87,90,91,94,104,108,110,113 Despite substantial differences in characteristics of the patient populations and in criteria for inclusion, numerous clinical studies of the incidence and Year(s) 1957-19671968-19701967-1971-1970Not stated 1966-19671960-1965-19711968-196419681970-197119701971-1967-1964 consequences of acute overdosage from around the world indicate that benzodiazepine ingestion accounts for a substantial proportion of cases of drug overdosage in adults (Table V). Findings from series describing time-related changes in patterns of drug ingestion…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 , 18 ] Canadian studies using Coroner’s data, death registries, and chart reviews provide limited information about the clinical circumstances of drug-related fatalities. [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of over 800 drug overdose cases admitted for emergency treatment in Hamilton, Ontario (Sims, Purdy, & Devenyi, 1973), it was found that among the adults, female overdosers far outnumbered the males. Alcohol or a history of alcoholism was frequently associated with the drug overdose.…”
mentioning
confidence: 99%